A Cognitive Study of FORCE Image Schemas - Szwedek, Aleksander (Theoria et Historia Scientiarum, 2023)
In my 2022 paper on Thematic roles in image schemas, I illustrated my 2019b image schema definition with two examples: MOTION and CONTAINER. The present paper tests yet another instance of a more complex nature, FORCE and its variations. Newton’s Third Law that “for every action, there is an equal and opposite reaction” means that all force variations have two force exerting objects in counterforce configuration. The relation between them can be viewed from the perspective of either one, or both, which is reflected in language structures. We experience force as intensity of contact with objects, associating it with their mass and velocity, and extrapolate our experience to external objects, assessing their force by velocity and mass. Following my 2019b definition of the image schema, and my 2022 suggestion on the function of Thematic roles in image schemas, the present paper critically reviews and reinterprets earlier analyses of forces.